Respon Pasar Terhadap Pengumuman Akuisisi pada Perusahaan Pengakuisisi yang Terdaftar di BEI Tahun 2013-2017 - Larasati, Putri; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 24 No 1 (2018)DO - 10.24843/EJA.2018.v24.i01.p19, 2018)
This study aims to obtain empirical evidence of market response on acquisitions announcement, investors will react and make changes in stock prices. The market response is measure d with abnormal return, which the difference between the expected return and the realization return. Abnormal return in this research is estimated by using market-adjusted model, which uses JCI data as calculation to get expected return. The type of research used is quantitative. The sample is determined through non probability method with purposive sampling technique. The number of companies used in this study amounted to 51 companies that do the acquisition which is a public company listing on the Indonesia Stock Exchange (IDX) period 2013-2017. This study uses one sample t-test. The results of this study indicate that there is no market response to the announcement of acquisitions on acquirer firm . This is evidenced by a significance of CAR 0.458 greater than 0.05. Keywords: abnormal return, market response, acquisitions